AST to Platelet Ratio Index and fibrosis 4 calculator scores for non-invasive assessment of hepatic fibrosis in patients with non-alcoholic fatty liver disease. Issue 10 (October 2017) - Peleg, Noam; Issachar, Assaf; Sneh-Arbib, Orly; Shlomai, Amir
Abstract: Background & aims: Liver fibrosis is the single most important prognostic factor in patients with non-alcoholic fatty liver disease (NAFLD). The predictive value of the AST to Platelet Ratio Index (APRI) score, originally developed for fibrosis assessment in hepatitis C virus (HCV) patients, is much less known in the context of NAFLD patients. Methods: We retrospectively compared the performance of APRI and fibrosis 4 calculator (FIB-4) scores in NAFLD patients with documented liver biopsies, to their performance in chronic HCV patients. Results: 153 patients with biopsy-proven NAFLD and 297 patients with biopsy-proven chronic HCV infection were included. The APRI score was a good predictor for advanced fibrosis in NAFLD patients (area under the ROC curve 0.8307) although it was modestly inferior as compared to the well-validated FIB-4 score (area under the ROC curve 0.8959). The predictive value of APRI score in NALFD patients was inferior as compared to its predictive value in HCV patients (area under the ROC curve of 0.8307 versus 0.9965). In contrast to FIB-4, APRI score was not a good discriminator between intermediate stages of fibrosis in NAFLD patients. Conclusions: APRI and Fib-4 scores are reasonable tools to allocate NAFLD patients with advanced fibrosis. FIB-4 may better discriminate between intermediate fibrosis stages.